Nerve Expansion Seen on Ultrasound Predicts Histologic But Not Functional Nerve Injury After Intraneural Injection in Pigs. Issue 2 (1st February 2010) - Lupu, Catalin Mario; Kiehl, Tim-Rasmus; Chan, Vincent W.S.; El-Beheiry, Hossam; Madden, Melissa; Brull, Richard
Abstract : Background and Objectives: Intraneural injection can be seen as nerve expansion during ultrasound-guided regional anesthesia. The purpose of this animal study was to determine if nerve expansion seen on ultrasound during intraneural injection results in nerve injury. Methods: Ten pigs underwent general anesthesia for this randomized control study. After skin incision, the right and left median nerves for each animal were randomly assigned to the local anesthetic (LA) side or control side. For the LA side, a needle was placed intraneurally under direct vision. Nerve expansion seen on ultrasound was produced by injecting up to 20 mL lidocaine 2% with epinephrine intraneurally. For the control side, no needle puncture or injection was administered. The primary outcome was histologic evidence of nerve injury (axonal retraction balls) on the seventh postoperative day after intraneural injection seen as nerve expansion on ultrasound. Correlation coefficients were calculated between the maximum volume injected, maximum injection pressure, degree of nerve expansion, and histologic and functional nerve injury. Results: Six nerves from the LA side and none from the control side had histologic evidence of injury ( P < 0.01). All 10 nerves from the LA side exhibited histologic evidence of inflammation compared with 3 from the control side ( P < 0.005). No pigs exhibited functional nerve injury. We were unable to demonstrate any correlation between the maximum volume injected or pressure generated and the relative increase in nerve cross-sectional area or the graded presence of any histologic markers of inflammation or injury. Conclusions: This animal study suggests that nerve expansion seen on ultrasound during intraneural injection of clinically relevant volumes of LA results in histologic but not functional nerve injury.